Σχεδίαση και Υλοποίηση 3D ηλεκτρονικού παιχνιδιού ενός παίκτη, κατηγορίας περιπέτειας-τρόμου - Κυριαζή, Στέλλα; Σαρέλα, Δήμητρα (Πανεπιστήμιο Πελοποννήσου, 2024)
This thesis analyses the main categories of computer games, with a greater emphasis on adventure and horror games. It presents the basic design concept of a first-person 3D adventure game with horror elements, and analyses the story, characters and main objectives of the game. It then details the steps of implementation of this idea, through the powerful game creation tool Unreal Engine, combining technical expertise and artistic vision. Finally, the challenges encountered during the implementation are highlighted, as well as the solutions applied to overcome them. This thesis presents a vision of future improvements to our game and explores possible routes for its evolution.
Μ.Δ.Ε. 55
Keywords: Εισαγωγή; Εισαγωγή στο Gaming; Σχεδιασμός; Υλοποίηση; Προκλήσεις-Μελλοντικές Βελτιστοποιήσεις; Συμπεράσματα; adventure game design; adventure game implementation; horror; single player; UE5; unreal engine; puzzles; game development